Satelite-derived assessment of rangeland productivity in Blouberg Municipality in a changing climate - Mashava, Thembani Theophilus (My University, 2025)
This study investigates rangeland productivity in Blouberg Municipality, Limpopo Province, under changing climatic conditions using satellite-derived data. The research employs MODIS-derived vegetation indices, specifically the Normalized Difference Vegetation Index (NDVI) and Enhanced Vegetation Index (EVI), to analyze trends in vegetation health from 2001 to 2022. By integrating climatic variables such as rainfall and temperature, the study assesses their impact on vegetation dynamics. Data processing was conducted using Google Earth Engine (GEE), enabling large-scale temporal monitoring of rangeland productivity. The findings reveal significant inter-annual variability in vegetation indices, driven primarily by climatic fluctuations. While the overall 20-year period does not exhibit a statistically significant long-term trend, selected years show significant variations, with p-values below 0.05. Notably, drought periods in 2002, 2005, and 2016 led to sharp declines in vegetation productivity, while post-drought recovery phases demonstrated the ecosystem's resilience. Correlation analysis confirmed a strong positive relationship between rainfall and vegetation indices, whereas temperature exhibited a weaker negative correlation. Additionally, the study identified specific areas within the municipality that are highly vulnerable to land degradation. These results underscore the critical need for adaptive land management strategies to sustain rangeland ecosystems in the face of climate variability. By providing valuable insights into vegetation-climate interactions and highlighting the significance of short-term climatic impacts, this research contributes to the development of evidence-based policies aimed at promoting the sustainable management of rangelands in semi-arid regions like Blouberg Municipality.
Thesis (M. Sc. (Geography and Environmental Studies)) -- University of Limpopo, 2025
Keywords: Rangeland productivity; Blouberg Municipality; Changing climate conditions; Satilite-derived data; Rangelands -- Monitoring; Range ecology; Agricultural productivity -- South Africa -- Limpopo; Agricultural innovations -- South Africa -- Limpopo; Climatic changes